2004
DOI: 10.1002/rcm.1655
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput chiral analysis of albuterol enantiomers in dog plasma using on‐line sample extraction/polar organic mode chiral liquid chromatography with tandem mass spectrometric detection

Abstract: An automated chiral chromatography/tandem mass spectrometry bioanalytical method for the determination of albuterol in dog plasma was developed. The method employed on-line sample extraction using turbulent flow chromatography coupled to a Chirobiotic T column for chiral separation using a polar organic mobile phase consisting of methanol, 0.02% formic acid, and 0.1% ammonium formate. The analytes were detected by a tandem mass spectrometer operated in positive ion mode. The (S)- and (R)-isomers were resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…L'autre limite se situe également au niveau de la durée de vie des colonnes d'extraction, mais celles-ci peuvent être préservées par une simple précipitation de l'échantillon biologique en amont de l'extraction en ligne, ce que nous réa-lisons systématiquement dans notre laboratoire. Cette précipi-tation préalable semble ainsi être le meilleur moyen pour allonger la durée de vie des colonnes d'extraction ainsi que le risque d'obstruction [1,18]. Enfin, l'acquisition d'un tel appareillage doit être rigoureusement étudié car relativement coû-teux à l'achat et en consommables et son investissement mé-rite d'être étudié sur le long terme en fonction des demandes adressées au laboratoire.…”
Section: Discussionunclassified
“…L'autre limite se situe également au niveau de la durée de vie des colonnes d'extraction, mais celles-ci peuvent être préservées par une simple précipitation de l'échantillon biologique en amont de l'extraction en ligne, ce que nous réa-lisons systématiquement dans notre laboratoire. Cette précipi-tation préalable semble ainsi être le meilleur moyen pour allonger la durée de vie des colonnes d'extraction ainsi que le risque d'obstruction [1,18]. Enfin, l'acquisition d'un tel appareillage doit être rigoureusement étudié car relativement coû-teux à l'achat et en consommables et son investissement mé-rite d'être étudié sur le long terme en fonction des demandes adressées au laboratoire.…”
Section: Discussionunclassified
“…Wu et al [13] used a similar set-up to analyze albuterol enantiomers, a drug used to help asthma patients, in dog plasma. They design a high throughput method with a sample turnout of 8 minutes.…”
Section: Plasma and Serum Samplementioning
confidence: 99%
“…Some of the reported methods for racemic salbutamol sulfate includes titrimetric (Basavaiah et al, 2006(Basavaiah et al, , 2007, potentiometric (Abdel-Ghani et al, 2002), spectrophotometric (Basavaiah et al, 2003(Basavaiah et al, , 2006(Basavaiah et al, , 2007Chitlange et al, 2011;Culzoni et al, 2006; Geeta et al ., 1989;Habib et al, 2004;Jain et al, 2011;Mishra et al, 2010;Parimoo et al, 1993;Rathore et al, 1993), spectrofluorimetric (Pandya et al, 2010), HPLC (Bernal et al, 1996;Boulton et al, 1995;Chitlange et al, 2011;Erram et al, 2006;Jain et al, 2011;Kasawar et al, 2010;Kountourellis et al, 1990;Martis et al, 2011;Murtaza et al, 2009;Pai et al, 2009) and LC-MS (Joyce et al, 1998;Wu et al, 2004Wu et al, , 2011Yee et al, 2011). Whereas for levosalbutamol sulfate a few spectrophotometric Thulasama et al, 2009) and HPLC (Ghemud et al, 2012;Halabi et al, 2004; methods are reported.…”
Section: Introductionmentioning
confidence: 99%